Trajectories of Depressed Mood and Anxiety During Chemotherapy for Breast Cancer. Issue 1 (January 2020) - Whisenant, Meagan; Wong, Bob; Mitchell, Sandra A.; Beck, Susan L.; Mooney, Kathi
Abstract : Background: Women are at risk of mood disturbance during treatment for breast cancer. Objective: The aims of this study were to identify classes of women experiencing similar trajectories of depressed mood and anxiety while receiving chemotherapy for breast cancer and to determine associated antecedents and outcomes. The specific aims were to (1) determine the distinct trajectory classes associated with severity of depressed mood and anxiety reported by women undergoing cycles 2 and 3 of chemotherapy for breast cancer, (2) determine if class membership is associated with various antecedent variables, and (3) determine if class membership is associated with days of missed work and hours spent lying down. Methods: In a secondary analysis, classes were identified using Latent Growth Mixture Modeling. Antecedents and outcomes related to class membership were explored. Results: Participants (n = 166; mean age, 53 [SD, 10.8] years) were mostly white (91.46%); half had early-stage disease. Two trajectories of depressed mood and anxiety were identified. Receipt of doxorubicin was associated with the higher severity class for depressed mood ( P < .01) and anxiety ( P = .04). No college education ( P = .03) or spending more hours lying down ( P = .03) was associated with the higher severity class for anxiety. Conclusions: Distinct trajectories of mood disturbance are distinguished by baseline severity. Further study is needed to determine if biologic or genomic factors are associated with class membership. Implications for Practice: Identification of women at risk of mood disturbance may allow clinicians to intensify symptom management. Mood disturbance early in the treatment trajectory warrants management to improve outcomes.